2008
DOI: 10.3899/jrheum.080220
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Deficiency and Defective Intracrine Processing of Dehydroepiandrosterone in Salivary Glands in Sjögren’s Syndrome

Abstract: DHEA and DHT upregulate CRISP-3, which is reportedly low in SS. The effect of DHEA on CRISP-3 is indirect and is inhibited by dutasteride, showing that there is intracrine processing of DHEA in salivary glands. In healthy glands, but not in SS, DHEA is effectively taken up and converted to DHT. Sex steroid concentrations in saliva in part reflect glandular uptake of DHEA-sulfate and local intracrine DHEA metabolism, which seem to be defective in SS. Our study demonstrates a prominent androgen deficiency and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 16 publications
5
34
0
Order By: Relevance
“…These circulating precursors are the primary substrate for androgen synthesis in peripheral tissues, and this intracrine production generates the vast majority of androgens in women [58, 59]. Disruption of this intracrine process has also been found in SS, leading to further androgen insufficiency [60]. …”
Section: Discussionmentioning
confidence: 99%
“…These circulating precursors are the primary substrate for androgen synthesis in peripheral tissues, and this intracrine production generates the vast majority of androgens in women [58, 59]. Disruption of this intracrine process has also been found in SS, leading to further androgen insufficiency [60]. …”
Section: Discussionmentioning
confidence: 99%
“…Further, DHEA and DHT increased CRISP3 protein concentration and the effect of DHEA on CRISP3 could be inhibited with dutasteride [24], which is a dual 5a-reductase inhibitor. These findings suggest ineffective conversion of DHEA to testosterone and DHT.…”
Section: Local Intracrine Derangement In Ssmentioning
confidence: 98%
“…The above mentioned derangement of the steroidogenic, DHEA metabolizing enzymes in human LSGs seems to be reflected in low salivary steroid hormone concentrations [24] and in the inability to convert DHEA to various sex steroids during DHEA substitution treatment [25]. Further, DHEA and DHT increased CRISP3 protein concentration and the effect of DHEA on CRISP3 could be inhibited with dutasteride [24], which is a dual 5a-reductase inhibitor.…”
Section: Local Intracrine Derangement In Ssmentioning
confidence: 99%
“…Indeed, in vitro experiments have shown that inhibition of 5a-reductase by dutasteride completely blocked the DHEA-induced up-regulation of CRISP-3 but did not affect DHT-induced up-regulation of CRISP-3 [15]. One of the reasons to this may be that the benign prostate hyperplasia is usually treated with finasteride, which inhibits 5a-reductase type 2 in the stromal cells of prostate.…”
Section: Why Women -Why Not Men?mentioning
confidence: 99%